[Review into the risks of fraud and corruption in local government procurement : A commitment from the UK Anti-Corruption Strategy 2017-2022].: A commitment from the UK Anti-Corruption Strategy 2017-2022]. Powers used by local authorities in England in relation to procurement fraud and corruption investigations. [Annex 8], (2020) - Unknown
No abstract available